Synchronization technology for OFDM system and its FPGA design - Xiao-kun Zheng; Cai-xia Li; Hai-nan Long; Shuang-li Geng; Zhi-qiang Liu (IET 3rd International Conference on Wireless, Mobile and Multimedia Networks (ICWMMN 2010), 2010)
For one of the focus communication technology, Multicarrier modulation OFDM (Orthogonal Frequency Division Multiplexing), this paper, based on the previous study of basic modem module, carry out some research on its key synchronization technology. The key point includes adding cyclic prefix and suffix to reduce requirement on accuracy of symbol synchronization, FFT window synchronization time and adding the training sequence to extract bit synchronization signal . In our subject study, algorithm is researched based on MATLAB language. And also introduces several considerations in FPGA circuit Hardware implementation.